Al-Jaghmını’s Short Tract on the Volumes of the Planetary and Stellar Bodies: Editio princeps and Translation - Sally P. Ragep (Nazariyat: Journal for the History of Islamic Philosophy and Sciences)
This article examines and provides an Arabic critical edition and English translation of the short tract attributed to Mahmūd al-Jaghmīnī (fl. 600/1200) that deals with the volumes of the celestial bodies and that may have been intended as a supplement to al-Mulakhkhas, his introduction to Ptolemaic theoretical astronomy. The work focuses on the sizes of the planetary bodies without addressing distances. The reader is provided with various lists such as which planetary bodies are above and below the Sun, the rounded volumes of bodies compared to the Earth, their sizes in descending order according to these volumes, and the body size of each measured in cubic parasangs (this being a mathematical calculation based on a derived parasang value for the Earth’s volume and the stated relative volume for each body). No sources are mentioned in the witnesses; however, Jaghmīnī evidently chose modified Ptolemaic values, despite the availability of both the Almagest and Planetary Hypotheses in the 13th century. Whether Jaghmīnī considered intermediary sources to be authentic Ptolemaic values or not is unclear. Three of the four manuscript witnesses used for the edition also include a brief additional section on measurement, which is an excerpt from Sinān Pāshā’s 15th-century gloss on Qāḍīzāde’s commentary on al-Mulakhkhas.